Effect of continuous magnesium sulfate infusion on spinal block characteristics: A prospective study - Agrawal, Akansha (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Spinal anesthesia is an established mode of anesthesia for lower limb orthopedic surgeries. The limitations of the technique are short duration of action and limited post-operative analgesia. Concomitant use of intravenous infusion of magnesium sulfate may have an effect on the block characteristics and duration of action of intrathecal bupivacaine. METHODS: A total of 80 American Society of Anesthesiologists I and II patients, either sex, 20-60 years of age scheduled for elective orthopedic fixation of fracture of long bones of lower limbs under spinal anesthesia were included. Spinal anesthesia administered with 2.5 ml heavy bupivacaine mixed with 10 mcg fentanyl. The groups were then divided to receive an infusion of injection magnesium sulfate 50 mg/kg/h over 15 min followed by 15 mg/kg/h until the end of the surgery (Group M) and 15 ml of Normal Saline over 15 min followed by 100 ml/h until the end of surgery (Group S). Onset, duration of sensory and motor block and amount of post-operative analgesic were noted. RESULTS: A total of 6 patients (Group M) and seven patients (Group S) had inadequate block and excluded from the study. Mean block height was T6. Time required to achieve block height was 8.82 min versus 7.42 min in Groups M and S respectively (P = 0.04). Mean duration of motor block was longer in group M (160.63 ± 17.76 min) compared with Group S (130.12 ± 20.70 min) (P = 0.000). Time for regression of sensory block to T12/L1was 206.88 ± 20.96 min (Group M) and 163.88 ± 15.46 min (Group S) (P = 0.000). Hemodynamic parameters were similar and statistically not significant. Need for first analgesic requirement was after 262.88 ± 21.11 min in group M and 193.25 ± 17.74 min in the group S (P = 0.000). Mean dosage of tramadol needed in first 24 h was less in group M (190 ± 30.38 mg vs. 265 ± 48.30 mg, P = 0.000). CONCLUSION: Use of intravenous magnesium with spinal anesthesia reduces post-operative pain and analgesic consumption.